House of the people? Afghanistan's parliament in 2015. Issue 6 (1st November 2016) - Larson, Anna
Abstract: Afghanistan's parliamentary elections in September 2005 marked the re-establishment of the legislature after a 30-year hiatus. Instead of connecting constituents to central government, however, it is argued here the Wolesi Jirga (lower house or WJ) has undermined accountability structures. This article analyses parliamentary processes by focusing on two examples of legislation that appeared in successive plenary debates in 2013 (the Elimination of Violence Against Women (EVAW) law and the electoral law). It argues, first, that Members of Parliament deploy political ambiguity in order to keep their political options open, simultaneously evading mechanisms that could hold them to account for their actions in parliament. Second, that historically and today, MPs' role in Afghanistan has been less one of advancing legislation than advocating on the behalf of localised support bases. Third, however, that most damaging to parliamentary accountability are elite attempts to control the political process amid free-flowing resources. The article discusses the implications of these features and how they are gendered in relation to women's strategic interests as well as behavioural roles of women MPs.